Tamil Nadu Logo
Board Tamil Nadu State Board [Samacheer Kalvi]
Class 10th Standard
Subject Maths
Medium English
Chapter Chapter 1 [Relations and Functions]
Exercise 1.5
Download Book Exercise Answers [Guide]

Samacheer Kalvi 10th Maths Chapter 1 [Exercise 1.5]

The notion of sets provides the stimulus for learning higher concepts in mathematics. A set is a collection of well-defined objects. This means that a set is merely a collection of something which we may recognize. In this chapter, we try to extend the concept of sets in two forms called Relations and Functions. For doing this, we need to first know about cartesian products that can be defined between two non-empty sets.

Download Samacheer Kalvi 10th Maths Guide [English Medium] Here

Samacheer Kalvi 10th Maths Chapter 1 [Exercise 1.5] Answers

Question-1:
Using the functions f and g given below, find fog and gof Check whether fog = gof.

(i) f(x) = x – 6, g(x) = x2
(ii) f(x) = 2x, g(x) = 2x2 – 1
(iii) f(x) = x+63, g(x) = 3 – x
(iv) f(x) = 3 + x, g(x) = x – 4
(v) f(x) = 4x2 – 1,g(x) = 1 + x

Solution:
(i) f(x) = x – 6, g(x) = x2
fog = fog (x)
= f(g(x))
fog = f(x)2
= x2 – 6
gof = go f(x)
= g(x – 6)
= (x – 6)2
= x2 – 12x + 36
fog ≠ gof

(ii) f(x) = 2/x, g(x) = 2x2 – 1
fag = f[g (x)]
= f(2/x2 – 1)
= 2/2x2−1
gof = g [f(x)]
= g (2x)
= 2 (2x)2 – 1
=2×4/x2−1
=8/x2−1
fog ≠ gof

(iii) f(x) = x+6/3, g(x) = 3 – x
fog = f[g(x)]
= f(3 – x)
=3-x+6/3
=9-x/3
gof = g [f(x)]
=g(x+6/3)
=3-(x+6)/3
=9-x-6/3
=3-x/3
fog ≠ gof

(iv) f(x) = 3 + x, g(x) = x – 4
fog = f[g(x)]
= f(x – 4)
= 3 + x – 4
= x – 1
gof = g[f(x)]
= g(3 + x)
= 3 + x – 4
= x – 1
fog = gof

(v) f(x) = 4x2 – 1,g(x) = 1 + x
fog = f[g(x)]
= 4(1 + x)
= 4(1 + x)2 – 1
= 4[1 + x2 + 2x] – 1
= 4 + 4x2 + 8x – 1
= 4x2 + 8x + 3
gof = g [f(x)]
= g (4x2 – 1)
= 1 + 4x2 – 1
= 4x2
fog ≠ gof

Question-2:
Find the value of k, such that fog = gof
(i) f(x) = 3x + 2, g(x) = 6x – k
(ii) f(x) = 2x – k, g(x) = 4x + 5

Solution:
(i) f(x) = 3x + 2, g(x) = 6x – k
fog(x) = f(g(x)) = f(6x – k) = 3(6x – k) + 2
= 18x – 3k + 2 …………… (1)
gof(x) = g(f(x)) = g(3x + 2) = 6(3x + 2) – k
= 18x + 12 – k ……………. (2)
(1) = (2)
⇒ 18x – 3k + 2 = 18x + 12 – k
2k = -10
k = -5

(ii) f(x) = 2x – k, g(x) = 4x + 5
fog(x) = f(g(x)) = f(4x + 5) = 2(4x + 5) – k
= 8x + 10 – k ……………… (1)
gof(x) = g(f(x)) = g(2x – k) = 4(2x – k) + 5
= 8x – 4k + 5 ……………. (2)
(1) = (2)
⇒ 8x + 10 – k = 8x – 4k + 5
3k = -5
k = −5/3

Question-3:
If f(x) = 2x – 1, g(x) = x+12, show that f o g = g o f = x

Solution:
f(x) = 2x – 1 ; g(x) = x+12
fog = f[g(x)]
=f[x+1/2]
=2(x+1/2)-1
=x+1-1
=x

gof = g[f(x)]
=g(2x-1)
=2x-1+1/2
=2x/2
=x
fog=gof=x
Hence it is proved.

Question-4:
(i) If f (x) = x2 – 1, g(x) = x – 2 find a, if gof(a) = 1.
(ii) Find k, if f(k) = 2k – 1 and fof (k) = 5.

Solution:
(i) f(x) = x2 – 1, g(x) = x – 2
Given gof(a) = 1
gof(x) = g(f(x)
= g(x2 – 1) = x2 – 1 – 2
= x2 – 3
gof(a) ⇒ a2 – 3 = 1 =+ a2 = 4
a = ± 2

(ii) f(k) = 2k – 1
fo f(k) = 5
f(f(k)m = f(2k – 1) = 5
⇒ 2(2k – 1) – 1 = 5
4 k – 2 – 1 = 5 ⇒ 4k = 8
k = 2

Question-5:
Let A,B,C ⊂ N and a function f: A → B be defined by f(x) = 2x + 1 and g: B → C be defined by g(x) = x2 . Find the range of fog and gof.

Solution:
f(x) = 2x + 1 ; g(x) = x2
fog = f[g(x)]
= f(x2)
= 2x2 + 1
2x2 + 1 ∈ N
g o f = g [f(x)]
= g (2x + 1)
g o f = (2x + 1)2
(2x + 1)2 ∈ N
Range = {y/y = 2x2 + 1, x ∈ N};
{y/y = (2x + 1)2, x ∈ N)

Question-6:
If f(x) = x2 – 1. Find (i)f(x) = x2 – 1, (ii)fofof

Solution:
(i) f(x) = x2 – 1
fof(x) = f(fx)) = f(x2 – 1)
= (x2 – 1 )2 – 1;
= x4 – 2x2 + 1 – 1
= x4 – 2x2

(ii) fofof = f o f(f(x))
= f of (x4 – 2x2)
= f(f(x4 – 2x2))
= (x4 – 2x2)2 – 1
= x8 – 4x6 + 4x4 – 1

Question-7:
If f : R → R and g : R → R are defined by f(x) = x5 and g(x) = x4 then check if f, g are one – one and fog is one – one?

Solution:
f(x) = x5 – It is one – one function
g(x) = x4 – It is one – one function
fog = f[g(x)]
= f(x4)
= (x4)5
fag = x20
It is also one-one function.

Question-8:
Consider the functions f(x), g(x), h(x) as given below. Show that (fog)oh = fo(goh) in each case.
(i) f(x) = x – 1, g(x) = 3x + 1 and h(x) = x2
(ii) f(x) = x2, g(x) = 2x and h(x) = x + 4
(iii) f(x) = x – 4, g(x) = x2 and h(x) = 3x – 5

Solution:
(i) f(x) = x – 1, g(x) = 3x + 1 and h(x) = x2
f(x) = x – 1
g(x) = 3x + 1
f(x) = x2
(fog)oh = fo(goh)
LHS = (fog)oh
fog = f(g(x)) = f(3x + 1) = 3x + 1 – 1 = 3x
(fog)oh = (fog)(h(x)) = (fog)(x2 ) = 32 ……………. (1)
RHS = fo(goh)
goh = g(h(x)) = g(x2) = 3x2 + 1
fo(goh) = f(3x2 + 1) = 3x2 + 1 – 1= 3x2 ………… (2)
LHS = RHS Hence it is verified.

(ii) f(x) = x2, g(x) = 2x, h(x) = x + 4
(fog)oh = fo(goh)
LHS = (fog)oh
fog = f(g(x)) = f(2x) = (2x)2 = 4x2
(fog)oh = (fog) h(x) = (fog) (x + 4)
= 4(x + 4)2 = 4(x2 + 8x+16)
= 4x2 + 32x + 64 ………….. (1)
RHS = fo(goh) goh = g(h(x)) = g(x + 4)
= 2(x + 4) = (2x + 8)
fo(goh) = f(goh) = f(2x + 8) = (2x + 8)2
= 4x2 + 32x + 64 ……………… (2)
(1) = (2)
LHS = RHS
∴ (fog)oh = fo(goh) It is proved.

(iii) f(x) = x – 4, g(x) = x2, h(x) = 3x – 5
(fog)oh = fo(goh)
LHS = (fog)oh
fog = f(g(x)) = f(x2) = x2 – 4
(fog)oh = (fog)(3x – 5) = (3x – 5)2 – 4
= 9x2 – 30x + 25 -4
= 9x2 – 30x + 21 ………….. (1)
∴ RHS = fo(goh)
(goh) = g(h(x)) = g(3x – 5) = (3x – 5)2
= 9x2 – 30x + 25
fo(goh) = f(9x2 – 30 x + 25)
= 9x2 – 30x + 25 – 4
= 9x2 – 30x + 21 …………… (2)
(1) = (2)
LHS = RHS
∴ (fog)oh = fo(goh)
It is proved.

Question-9:
Let f = {(-1, 3), (0, -1), (2, -9)} be a linear function from Z into Z. Find f(x).

Solution:
The linear equation is f(x) = ax + b
f(-1) = 3
a(-1) + b = 3
-a + b = 3 ….(1)
f(0) = -1
a(0) + b = -1
0 + b = -1
b = -1
Substitute the value of b = -1 in (1)
-a – 1 = 3
-a = 3 + 1
-a = 4
a = -4
∴ The linear equation is -4(x) -1 = -4x – 1 (or) – (4x + 1)

Question-10:
In electrical circuit theory, a circuit C(t) is called a linear circuit if it satisfies the superposition principle given by C(at1 + bt2) = aC(t1) + bC(t2), where a,b are constants. Show that the circuit C(t) = 31 is linear.

Solution:
Given C(t) = 3t. To prove that the function is linear
C(at1) = 3a(t1)
C(bt2) = 3 b(t2)
C(at1 + bt2) = 3 [at1 + bt2] = 3at1 + 3bt2
= a(3t1) + b(3t2) = a[C(t1) + b(Ct2)]
∴ Superposition principle is satisfied.
Hence C(t) = 3t is linear function.

Download Samacheer Kalvi 10th Maths Chapter 1 [Exercise 1.5] Answers

Download Samacheer Kalvi 10th Maths Chapter 1 Relations and Functions [Exercise 1.5] Answers [Guide] PDF

Exercise 1.5 Answers Download Here

Have a question? Please feel free to reach out by leaving a comment below

(Visited 32 times, 1 visits today)

Leave a Reply

Your email address will not be published. Required fields are marked *